2020
DOI: 10.1101/2020.06.21.162396
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Calcitriol, the active form of vitamin D, is a promising candidate for COVID-19 prophylaxis

Abstract: COVID-19, the disease caused by SARS-CoV-2 (1), was declared a pandemic by the World Health Organization (WHO) in March 2020 (2). While awaiting a vaccine, several antivirals are being used to manage the disease with limited success (3, 4). To expand this arsenal, we screened 4 compound libraries: a United States Food and Drug Administration (FDA) approved drug library, an angiotensin converting enzyme-2 (ACE2) targeted compound library, a flavonoid compound library as well as a natural product library. Of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 21 publications
(11 reference statements)
0
51
0
1
Order By: Relevance
“…This mechanism may be relevant in COVID-19 as low plasma levels of vitamin D are reported in SARS-CoV-2 infected individuals and significantly contribute to the risk of infection and hospitalization ( Merzon et al., 2020 ). Calcitriol, the active form of vitamin D, is also reported to directly reduce the virus-induced cytopathic effect of SARS-CoV-2 infection in cultured human respiratory epithelial cells ( Mok et al., 2020 ). The combination of melatonin and vitamin D has been proposed as a potentially synergistic intervention in COVID-19 ( Martín Giménez et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism may be relevant in COVID-19 as low plasma levels of vitamin D are reported in SARS-CoV-2 infected individuals and significantly contribute to the risk of infection and hospitalization ( Merzon et al., 2020 ). Calcitriol, the active form of vitamin D, is also reported to directly reduce the virus-induced cytopathic effect of SARS-CoV-2 infection in cultured human respiratory epithelial cells ( Mok et al., 2020 ). The combination of melatonin and vitamin D has been proposed as a potentially synergistic intervention in COVID-19 ( Martín Giménez et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, while existing data had already shown that vitamin D enhances the anti-viral activity of bronchial epithelial cells in vitro [39], recent research examining 2191 candidate compounds also identified a potential role for vitamin D in the specific inhibition of Covid-19 viral replication. The authors of this study concluded that calcitriol exhibits "significant, potent anti-viral activity" against SARS-CoV-2 in cultured human nasal epithelial cells in vitro [40].…”
Section: Infectionmentioning
confidence: 92%
“…Recently, Mok et al . [8] extended this line of research to SARS‐CoV‐2, the cause of COVID‐19. They demonstrated for the first time that calcitriol, the active form of vitamin D, exhibits potent activity against SARS‐CoV‐2.…”
Section: The Role Of Vitamin D In the Covid‐19 Pandemicmentioning
confidence: 99%